Long‐term evaluation of fitness and demographic effects of a Chinook Salmon supplementation program. (15th November 2018) - Janowitz‐Koch, Ilana; Rabe, Craig; Kinzer, Ryan; Nelson, Doug; Hess, Maureen A.; Narum, Shawn R.
Abstract: While the goal of supplementation programs is to provide positive, population‐level effects for species of conservation concern, these programs can also present an inherent fitness risk when captive‐born individuals are fully integrated into the natural population. In order to evaluate the long‐term effects of a supplementation program and estimate the demographic and phenotypic factors influencing the fitness of a threatened population of Chinook Salmon ( Oncorhynchus tshawytscha ), we genotyped tissue samples spanning a 19‐year period (1998–2016) to generate pedigrees from adult fish returning to Johnson Creek, Idaho, USA. We expanded upon previous estimates of relative reproductive success (RRS) to include grandparentage analyses and used generalized linear models to determine whether origin (hatchery or natural) or phenotypic traits (timing of arrival to spawning grounds, body length, and age) significantly predicted reproductive success (RS) across multiple years. Our results provide evidence that this supplementation program with 100% natural‐origin broodstock provided a long‐term demographic boost to the population (mean of 4.56 times in the first generation and mean of 2.52 times in the second generation). Overall, when spawning in nature, hatchery‐origin fish demonstrated a trend toward lower RS compared to natural‐origin fish ( p < 0.05). However, when hatchery‐origin fish successfully spawned with natural‐origin fish, they had similar RS compared to natural by natural crosses (first‐generation mean hatchery by natural cross RRS = 1.11 females, 1.13 males; second‐generation mean hatchery by natural cross RRS = 1.03 females, 1.08 males). While origin, return year, and body length were significant predictors of fitness for both males and females ( p < 0.05), return day was significant for males but not females ( p > 0.05). These results indicate that supplementation programs that reduce the potential for genetic adaptation to captivity can be effective at increasing population abundance while limiting long‐term fitness effects on wild populations.